Alantolactone: A Potential Multitarget Drug candidate for Prevention of SARS-CoV-2 Cell Entry - Erum Zafar; Zainab Ahsan; Muhammad Faisal Maqbool; Aqsa Zaman; Sameena Gul; Amara Maryam; Muhammad Khan; Hafiz Abdullah Shakir; Muhammad Irfan (Journal of Molecular Docking, 2022)
The novel strain of coronavirus, SARS-CoV-2, has spread adverse effects on human health with high mortality rates worldwide. SARS-CoV-2 is a severe respiratory disease expressed through positive single stranded RNA enveloped virus. SARS-CoV-2 had affected globally and is influencing the economy as well. The rapidly spreading coronavirus infection has discombobulated the researchers in perpetuate search for different or effective therapeutic drugs.  Most of the connatural products are proposed to have significant clinical outcomes but their pathways of action are not clear. This molecular docking study presents alantolactone, a bio-active member of sesquiterpene family as a successful inhibitor of SARS-Cov-2 and human receptor proteins. Alantolactone shows high binding affinity with the SARS-CoV-2 target proteins such as spike glycoprotein (S-protein), nucleocapsid protein (N-protein), main protease (MPro), and papain-like protease (PLPro) with a binding affinity of -7.3 kcal/mol, -7.9 kcal/mol, -6.8 kcal/mol, and -7.1 kcal/mol, respectively as well as human receptor  proteins associated with the recognition, binding and biogenesis of SARS-CoV-2 such as angiotensin-converting enzyme 2 (ACE-2), receptor binding domain (S1-RBD) and ACE2 interphase, furin, adaptor-associated protein kinase 1 (AAK1), cyclin G-associated kinase (GAK), and both closed and open configurations of the two-pore channel (TPC2) with binding energies of -6.7 kcal/mol, - 6.9 kcal/mol, -8.1 kcal/mol, -7.3 kcal/mol, and -7.9 kcal/mol, respectively. Molecular docking and ADMET properties and toxicity predictions suggest that alantolactone could effectively binds with various viral target protein and human target proteins and could be developed into a novel SARS-coV-2 inhibitor.